GIGANTEA Regulates the Timing Stabilization of CONSTANS by Altering the Interaction between FKF1 and ZEITLUPE - Hwang, Dae Yeon; Park, Sangkyu; Lee, Sungbeom; Lee, Seung Sik; Imaizumi, Takato; Song, Young Hun (Molecules and Cells, 2019)
Plants monitor changes in day length to coordinate their flowering time with appropriate seasons. In Arabidopsis, the diel and seasonal regulation of CONSTANS (CO) protein stability is crucial for the induction of FLOWERING LOCUS T (FT) gene in long days. FLAVIN-BINDING, KELCH REPEAT, F-BOX 1 (FKF1) and ZEITLUPE (ZTL) proteins control the shape of CO expression profile antagonistically, although regulation mechanisms remain unknown. In this study, we show that GIGANTEA (GI) protein modulates the stability and nuclear function of FKF1, which is closely related to the stabilization of CO in the afternoon of long days. The abundance of FKF1 protein is decreased by the gi mutation, but increased by GI overexpression throughout the day. Unlike the previous report, the translocation of FKF1 to the nucleus was not prevented by ZTL overexpression. In addition, the FKF1-ZTL complex formation is higher in the nucleus than in the cytosol. GI interacts with ZTL in the nucleus, implicating the attenuation of ZTL activity by the GI binding and, in turn, the sequestration of FKF1 from ZTL in the nucleus. We also found that the CO-ZTL complex presents in the nucleus, and CO protein abundance is largely reduced in the afternoon by ZTL overexpression, indicating that ZTL promotes CO degradation by capturing FKF1 in the nucleus under these conditions. Collectively, our findings suggest that GI plays a pivotal role in CO stability for the precise control of flowering by coordinating balanced functional properties of FKF1 and ZTL.
Keywords: Arabidopsis; Arabidopsis Proteins; Cell Nucleus; DNA-Binding Proteins; Gene Expression Regulation, Plant; Photoperiod; Protein Binding; Protein Stability; Time Factors; Transcription Factors; CONSTANS; FKF1; flowering; GIGANTEA; ZEITLUPE